2010
DOI: 10.1111/j.1745-3933.2009.00807.x
|View full text |Cite
|
Sign up to set email alerts
|

First spatial resolution of the stellar components of the interacting binary CH Cygni

Abstract: We report the first resolved bispectrum speckle interferometry of the symbiotic binary CH Cyg. The measured component separation, ρ= 42 ± 2 mas, is consistent with the one derived from the known spectroscopic orbit and distance. In particular, our result implies a total mass of the binary of Mt=Mg+Mwd= 3.7+3.5−1.7 M⊙, which is in good agreement with the value Mt= 2.7+1.2−0.6 M⊙ derived from the spectroscopic orbit solution for the red giant and evolutionary constraints. We also show that the radio jets and the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The binary system was resolved for the first time (the components are separated by 42 ± 2 mas) by Mikołajewska et al (2010), giving a total binary mass of about 3.7 M ⊙ , in good agreement with the mass resulting from the spectroscopic orbit derived by Hinkle et al (2009). The distance estimated by Mikołajewska et al (2010) 220 +40 −28 pc is consistent with the new value 205 +3 −4 pc derived by Gaia DR 3 (Table B1) as well as with the previous Hipparcos result 244 +49 −35 pc.…”
Section: A8 Ch Cygmentioning
confidence: 99%
See 1 more Smart Citation
“…The binary system was resolved for the first time (the components are separated by 42 ± 2 mas) by Mikołajewska et al (2010), giving a total binary mass of about 3.7 M ⊙ , in good agreement with the mass resulting from the spectroscopic orbit derived by Hinkle et al (2009). The distance estimated by Mikołajewska et al (2010) 220 +40 −28 pc is consistent with the new value 205 +3 −4 pc derived by Gaia DR 3 (Table B1) as well as with the previous Hipparcos result 244 +49 −35 pc.…”
Section: A8 Ch Cygmentioning
confidence: 99%
“…The binary system was resolved for the first time (the components are separated by 42 ± 2 mas) by Mikołajewska et al (2010), giving a total binary mass of about 3.7 M ⊙ , in good agreement with the mass resulting from the spectroscopic orbit derived by Hinkle et al (2009). The distance estimated by Mikołajewska et al (2010) 220 +40 −28 pc is consistent with the new value 205 +3 −4 pc derived by Gaia DR 3 (Table B1) as well as with the previous Hipparcos result 244 +49 −35 pc. The 2MASS magnitudes of CH Cyg, 𝐽 = 1.07 ± 0.29 and 𝐾 = −0.42 ± 0.19 are in fairly good agreement with with 𝐽 = 1.14 ± 0.09, 𝐾 = −0.43 ± 0.13 (Ananth & Leahy 1993) and 𝐽 ∼ 492 Jy, 𝐾 ∼ 953 Jy (Price et al 2010), which when converted with the use of calibrations by Jarrett et al (2011) and Bessell et al (1998) give equivalent magnitudes 𝐽 ∼ 1.25 and 𝐾 ∼ −0.44, respectively.…”
Section: A8 Ch Cygmentioning
confidence: 99%
“…The equivalent widths of Hβ and [O III] 5007 were −10.8 Å and −2.3 Å at that date. Mikolajewska et al (2010) estimated the luminosity of the faint object to have been about 2 mag fainter than the M-type giant in the optical region. They claimed that CH Cyg was in a mild active stage because the emission lines of H I, Fe II, and [O III] were detected (Yoo 2007), and therefore the hot component had a high luminosity in the optical region.…”
Section: Radial Velocities Of Absorption and Emissionmentioning
confidence: 99%
“…Balega et al (2007) performed interferometric observations in October 2004 and found a faint object of 43 or 41 milliarcseconds (mas) detached from the M-type giant. Detailed analyses of their images were made by Mikolajewska et al (2010) who concluded that the faint object was the hot component on the outer orbit with the period of 15 years. Such an object, however, was not confirmed by the infrared interferometry performed by Pedretti et al (2009) in the same year.…”
Section: Radial Velocities Of Absorption and Emissionmentioning
confidence: 99%
“…CH Cyg is an eclipsing symbiotic star composed of a M6-7 III star and an accreting white dwarf, so the system belongs to the S-type symbiotics. The binary separation is 8.7 +1.1 −0.7 AU (Miko lajewska et al, 2010). The masses of the components are M rg = 2 +1 −0.5 M ⊙ and M wd = 0.70 +0.22 −0.09 M ⊙ (Miko lajewska et al, 2010).…”
Section: Introductionmentioning
confidence: 99%